Desenvolvimento de nanocompósitos baseados em hidrogéis aplicados à liberação de nutrientes agrícolas - Bortolin, Adriel (2014)
Nanocomposites were developed based on polyacrylamide hydrogels (PAAm) and methylcellulose (MC) reinforced with montmorillonite (MMT), undergoing the materials to subsequent hydrolysis process and evaluating their loading and potential for slow release of agricultural nutrients. The hydrolyzed material obtained excellent results in terms of swelling degree, about five times higher than hydrogels commonly found in the literature and presented loading capacity values of two sources of nutrients - urea (macronutrient) and sodium octaborate (micronutrient) - above to the generally reported. Finally, it was shown that the nanocomposites structure played a key role to control the release of nutrient sources, whereas the MMt content in the material controlled the total amount charged and reduced the release kinetics of nutrient for solution. Through X-ray diffraction, good nanodispersion (intercalation) and exfoliation of the clay platelets in the polymeric hydrogel matrix were revealed, mainly for the hydrolyzed nanocomposites. FTIR analysis indicated that incorporation of the MMt with the polymer matrix of the hydrogel occurred, and this incorporation increased the rate of water and nutrient solution absorption (indicated by higher values in kinetic constant k). The presence of MMt in the nanocomposite was shown as a decisive factor for the application viability, since it determined the increasing in mechanical strength, improved thermal properties and loading capacity for nutrient sources, also contributing significantly to the reduction of the final price of material. The results showed that nanocomposites are potentially applicable in agricultural systems as a carrier of nutrients sources.